Transfer of elements into boreal forest ants at a former uranium mining site - Roivainen Päivi; Muurinen Saara-Maria; Sorvari Jouni; Juutilainen Jukka; Naarala Jonne; Salomaa Sisko (Elsevier Ltd, 2022)
Ants can influence ecological processes, such as the transfer of elements or radionuclides, in several ways. For example, they redistribute materials while foraging and maintaining their nests and have an important role in terrestrial food webs. Quantitative data of the transfer of elements into ants is needed, e.g., for developing improved radioecological models. In this study, samples of red wood ants (genus Formica), nest material, litter and soil were collected from a former uranium mining site in Eastern Finland. Concentrations of 33 elements were analyzed by Inductively Coupled Plasma-Mass Spectroscopy/Optical Emission Spectroscopy. Estimated element concentrations in spruce needles were used as a proxy for studying the transfer of elements into ants via aphids because spruces host the most important aphid farms in boreal forests. Empirically determined organism/medium concentration ratios (CRs) are commonly used in radioecological models. Ant/soil CRs were calculated and the validity of the fundamental assumption behind the of use of CRs (linear transfer) was evaluated. Elements that accumulated in ants in comparison to other compartments were cadmium, potassium, phosphorus, sulfur, and zinc. Ant uranium concentrations were low in comparison to soil, litter, or nest material but slightly elevated in comparison to spruce needles. Ant element concentrations were quite constant regardless of the soil concentrations. Non-linear transfer models could therefore describe the soil-to-ant transfer better than conventional CRs.